Interactive effects of competition and social environment on the expression of sexual dimorphism. (13th May 2014) - De Lisle, S. P.; Rowe, L.
Abstract The expression of sexual dimorphism is expected to be influenced by the acquisition of resources available to allocate to trait growth, combined with sex‐specific patterns of resource allocation. Resource acquisition in the wild may be mediated by a variety of ecological factors, such as the density of interspecific competitors. Allocation may in turn depend on social contexts, such as sex ratio, that alter the pay‐off for investment in sexual traits. How these factors interact to promote or constrain the expression and evolution of sexual dimorphism is poorly understood. We manipulated sex ratio and interspecific resource competition over the growing season of red‐spotted newts (Notophthalmus viridescens) in artificial ponds. Fish competitors had a stronger effect on female than male growth, which effectively eliminated the expression of sexual size dimorphism. In addition, newt sex ratio influenced fish growth, leading to reduction in fish mass with an increase in female newt frequency. Fish also reduced the expression of male tail height, a sexually selected trait, but only in tanks with a female‐biased sex ratio. This suggests males alter their resource allocation pattern in response to the strength of sexual selection. Our results demonstrate that ecologically and socially mediated interactions between sex‐specific resource acquisition and allocation can contribute to variation in the expression of sexual dimorphism.